GENDER EDUCATION OF SENIOR PRESCHOOLERS IN INSTITUTION OF PRESCHOOL EDUCATION - Lutsenko, Victoria (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article presents the theoretical and methodological principles of formation of senior preschoolers’ gender identity in the process of gender education in institution of preschool education. The purpose of the article is to present the results of research work on the process of formation of senior preschoolers’ gender identity in institution of preschool education. Among the main tasks were: 1) to clarify the essence, content of gender identity, identify and analyze its main components; 2) to substantiate the criteria and indicators for determining the levels of gender identity, to diagnose them; 3) to substantiate theoretically and to test experimentally the pedagogical conditions for the formation of senior preschoolers’ gender identity. All tasks were completed. In the process of research the following methods were used: theoretical – analysis of psychological and pedagogical literature to compare scientists’ views on the researched problem; comparison, classification, systematization and generalization of data to determine the essence, principles and methods of gender education and development of pedagogical recommendations in order to increase its effectiveness; empirical – pedagogical experiment, questionnaires, testing, interviews to study the components of gender education of senior preschoolers; questionnaires (for teachers and parents), conversation (for children) in order to identify the impact of factors of gender education; interactive methods for diversification of methods of educational influence and increase of its efficiency; the methods of mathematical statistics for quantitative and qualitative analysis of empirical data. The analysis of the received data allowed to allocate levels of formation of humane relations: low, average, optimum, high. The conclusions emphasize that the results of the study provide the effectiveness of the process of the formation of senior preschoolers’ gender identity in the process of education in institution of preschool education.